Comparative Assessment of the Acute Effects of Whey, Rice and Potato Protein Isolate Intake on Markers of Glycaemic Regulation and Appetite in Healthy Males Using a Randomised Study Design - Tiekou Lorinczova, Helena (Nutrients, 2021)
Global protein consumption has been increasing for decades due to changes in demographics and consumer shifts towards higher protein intake to gain health benefits in performance nutrition and appetite regulation. Plant-derived proteins may provide a more environmentally sustainable alternative to animal-derived proteins. This study, therefore, aimed to investigate, for the first time, the acute effects on glycaemic indices, gut hormones, and subjective appetite ratings of two high-quality, plant-derived protein isolates (potato and rice), in comparison to a whey protein isolate in a single-blind, triple-crossover design study with nine male participants (30.8 ± 9.3 yrs). Following a 12 h overnight fast, participants consumed an equal volume of the three isocaloric protein shakes on different days, with at least a one-week washout period. Glycaemic indices and gut hormones were measured at baseline, then at 30, 60, 120, 180 min at each visit. Subjective palatability and appetite ratings were measured using visual analogue scales (VAS) over the 3 h, at each visit. This data showed significant differences in insulin secretion with an increase in whey (+141.8 ± 35.1 pmol/L; p = 0.011) and rice (−64.4 ± 20.9 pmol/L; p = 0.046) at 30 min compared to potato protein. A significantly larger total incremental area under the curve (iAUC) was observed with whey versus potato and rice with p < 0.001 and p = 0.010, respectively. There was no significant difference observed in average appetite perception between the different proteins. In conclusion, this study suggests that both plant-derived proteins had a lower insulinaemic response and improved glucose maintenance compared to whey protein.